Allah, Al-Ilah, and Allahumma: The Arabic Language Usage before the 9th century AD in the Christian-Muslim Middle Eastern - Bulan, Susanti Embong; Prihantoro, Yogi; Missa, Antonius; Putrawan, Bobby Kurnia (the Faculty of Ushuluddin, UIN Sunan Gunung Djati Bandung, 2023)
This research investigates the usage of the terms Allah, Al-Ilah, and Allahumma in the Christian-Muslim Middle Eastern context before the 9th century AD. The aim of this study is to trace the historical development and theological implications of these terms within Arabic-speaking Christian and Muslim communities. The research method employed is a literature review, focusing on historical documents and inscriptions. The findings reveal that these terms were used in both religious traditions, indicating a shared linguistic and cultural heritage. Generalising these unique terms across both religions has been a major source of misunderstanding. This discussion remains relevant, not only in the context of Christian and Islamic religious language but also in the general use of Arabic within churches that use the Arabic language today, such as the Syrian and Coptic Churches in the Middle East. This article elucidates that Arab Christian communities are considered a missing link between the Christian and Islamic worlds. The research shows that the same ritual words—Allah, Al-Ilah, and Allahumma—were used before the advent of Islam. Through these Arab Christian communities, various points of contact and examples of tolerance and understanding can be clearly developed. This study contributes to a foundational theological understanding shared between Christianity and Islam, fostering interfaith dialogue and mutual respect.